Early Childhood Caries dan Kualitas Hidup Anak - ., Jeffrey (Zenit, 2015)
The American Academy of Pediatric Dentistry (AAPD) recognizes Early Childhood Caries (ECC/nursing bottle caries) as a significant public health problem. Oral health care needs vary but encompass all ages. Poor oral health disproportionately affects people living in low socio-economic status environment and rural communities. Oral health may affect a childâs growth and development, its social behaviour, nutrition, learning and its overall well-being. ECC is 100% preventable,butmost parents often disagree with this statement. The consequences of ECC include a higher risk of new carious lesions in both the primary and permanent dentitions. ECC interferes not only with the quality of life of the child, but also of the family. It affects a childs school performance, and its socialbehaviour. Treatment of ECC is costly, invasive and stressful. Young children with high caries activity may develop caries even during tooth eruption; therefore, it is essential to reach for thepreschool children and their caregivers as early as possible. This research highlights the importance of eliminating the root causes of ECC, which will in turn help children to be as healthy as they can be. Treating dental caries in pre-school children would increase the growth rate and the quality of life ofmillions of children.Keywords: Early Childhood Caries (ECC), quality of life, children